Striking Differences in Regulating Effects on Electronic Transport of 2D Iodine-Based Devices from Metal and Nonmetal Dopants; Inorganic Chemistry; Vol. 64, iss. 9 - Liu Rukai; Jie Li; Kun Liu; Martyushev N. V. Nikita Vladimirovich (2025, 2025)
Title screen